Vulnerable children: Protection and social reintegration of child soldiers and youth members of gangs. (December 2020) - Garbarino, James; Governale, Amy; Nesi, Danielle
Abstract: In the 30 years since the adoption of the United Nation's Convention of the Rights of the Child (CRC), international policy and research has continuously examined the impact of community violence exposure on child development. This article uses the framework of the CRC to review how the world has studied the involvement of child soldiers in armed conflict. We then apply Article 38 of the CRC (which prohibits the use of child soldiers) to parallel the literature regarding youth involvement in gangs. We argue that due to high similarities of these groups, including in regards to risk factors, traumatic experiences, and post-experience sequelae, youth gang members should be included as a protected group under the CRC as are child soldiers. We conclude with a discussion of programs that may be effective at preventing recruitment into armed conflict and gang memberships, and programs that reduce traumatic symptoms of children who experience and perpetrate violence.